Une approche pluridisciplinaire et pluri-scalaire des dynamiques paysagères du bassin minier du Nord-Pas-de-Calais - Fabrice Raffin; Antoine Luginbühl; Olivier Pollet (VertigO)
The article addresses the complex dynamics of landscape observed on the territory of Henin Carvin’s urban area (Nord-Pas de Calais, France). Using a pluridisciplinary (landscape designers and sociologists) and participatory approach the article goes beyond the consensual vision of landscape as a “social construction” and investigates the role of the diverse land-use planning actors (public decision makers, civil society, private firms). We here consider landscape as a thinking framework and tool that help to develop territorial action in a planned and sustainable manner. The identification of the diversity of planning actors and the understanding of their motivation and behavior provide a baseline for collective questioning of the dynamics of landscape we observe.